Genome-wide association study identifies genetic loci associated with iron deficiency. - Christine E McLaren; Chad P Garner; Clare C Constantine; Stela McLachlan; Chris D Vulpe; Beverly M Snively; Victor R Gordeuk; Debbie A Nickerson; James D Cook; Catherine Leiendecker-Foster; Kenneth B Beckman; John H Eckfeldt; et al. (PLoS ONE)
The existence of multiple inherited disorders of iron metabolism in man, rodents and other vertebrates suggests genetic contributions to iron deficiency. To identify new genomic locations associated with iron deficiency, a genome-wide association study (GWAS) was performed using DNA collected from white men aged≥25 y and women≥50 y in the Hemochromatosis and Iron Overload Screening (HEIRS) Study with serum ferritin (SF)≤12 µg/L (cases) and iron replete controls (SF>100 µg/L in men, SF>50 µg/L in women). Regression analysis was used to examine the association between case-control status (336 cases, 343 controls) and quantitative serum iron measures and 331,060 single nucleotide polymorphism (SNP) genotypes, with replication analyses performed in a sample of 71 cases and 161 controls from a population of white male and female veterans screened at a US Veterans Affairs (VA) medical center. Five SNPs identified in the GWAS met genome-wide statistical significance for association with at least one iron measure, rs2698530 on chr. 2p14; rs3811647 on chr. 3q22, a known SNP in the transferrin (TF) gene region; rs1800562 on chr. 6p22, the C282Y mutation in the HFE gene; rs7787204 on chr. 7p21; and rs987710 on chr. 22q11 (GWAS observed P<1.51×10(-7) for all). An association between total iron binding capacity and SNP rs3811647 in the TF gene (GWAS observed P=7.0×10(-9), corrected P=0.012) was replicated within the VA samples (observed P=0.012). Associations with the C282Y mutation in the HFE gene also were replicated. The joint analysis of the HEIRS and VA samples revealed strong associations between rs2698530 on chr. 2p14 and iron status outcomes. These results confirm a previously-described TF polymorphism and implicate one potential new locus as a target for gene identification.